Glutathione in cancer progression and chemoresistance: an update - Giulia Elda Valenti; Bruno Tasso; Nicola Traverso; Cinzia Domenicotti; Barbara Marengo (Bioscientifica, 2024)
Glutathione (GSH) is one of the most important components of the cellular antioxidant system, and it is able to exert several pleiotropic functions i nfluencing cell growth, proliferation, adaptation and death. It has been demonstrated that changes in GSH levels underlie the pathogenesis of many human diseases, including cancer. In detail, although on one hand GSH homeostasis plays a protective role from the onset of cancer, on the other, it is involved in cancer progression and in therapy resi stance. In this review, after a brief report on the physiological role of GSH, we have focuse d the attention on its role in cancer and refractoriness to anticancer therapy giving an update on the preclinical and clinical studies relied on the compounds targeting GSH system. Based on these considerations, a deeper knowledge of GSH-dependent network can be crucial to identify new strategies for preventing and/or curing cancer.